Local Films or Hollywood Films: Malaysian’s Preferences - Sriganeshvarun, Nagaraj; Abdul Aziz, Mohd Mustafa (INTI International University, 2019)
Since nine decades Hollywood films dominate the film industry in majority of the countries. In Malaysia, from year 2012 until 2018 demand for Hollywood films are at least 50% higher compare to Local films. This study aims to find the reason behind it? Are all the Local films have low demand? The purpose of this paper is to investigate the reason why demand for Hollywood films is high. A Qualitative Interview method was used to collect data. Three prominent races of Malaysia were interviewed. Total 49 respondents, 13 from each race with both genders within Nilai, Negeri Sembilan . The reasons why people like to watch Hollywood films are quality of content, story line and characters, visual effects, Stardom. The respondents said that in the last 5 years that Malaysian film have improved and also suggested to include international actor, director and script writer in the production of local films that will boost the quality of Malaysian film.